Uncovering a reconstructive solid–solid phase transition in a metal–organic framework - L. Longley; N. Li; F. Wei; T. D. Bennett (Royal Society Open Science, 2017)
A nanoporous three-dimensional metal–organic framework (MOF), ZnPurBr undergoes a transition to a previously unreported high-temperature phase, ZnPurBr-ht. The transition, which proceeds without mass loss, is uncovered through the use of differential scanning calorimetry (DSC). The new crystal structure was solved using single-crystal X-ray diffraction, and the mechanical properties of both phases investigated by nanoindentation and density functional theory. The anisotropy of the calculated Young's moduli showed good agreement with the crystallographic alignment of the stiff purinate organic linker. The results provide a prototypical example of the importance of the use of DSC in the MOF field, where its use is not currently standard in characterization.